AI for Coherent Writing: Supporting EFL learners’ Text Structure Development - Mike Amelia; Fitri Handayani (English Language Education Department, Universitas Majalengka, 2025)
The integration of Artificial Intelligence (AI) into education has reshaped language learning, particularly in writing. This study examines the effect of AI-assisted writing analysis on the structural coherence of English as a Foreign Language (EFL) students’ academic essays. Using a quasi-experimental design, thirty undergraduate students at Universitas Terbuka participated in pre- and post-tests and completed a perception questionnaire based on the Technology Acceptance Model (TAM). Quantitative results revealed significant improvement in structural coherence, especially in organization and use of transitions. Students also reported high perceived usefulness and ease of use of AI tools. These findings suggest that AI-assisted feedback can effectively enhance writing coherence when integrated into process-oriented instruction, while emphasizing the need for teacher guidance and critical engagement. The study highlights the pedagogical and ethical implications of incorporating AI into higher education writing contexts.